A critical role for transforming growth factor-beta but not interleukin 4 in the suppression of T helper type 1-mediated colitis by CD45RB(low) CD4+ T cells. - Powrie, F; Carlino, J; Leach, M; Mauze, S; Coffman, R (1996)
A T helper type 1 (Th1)-mediated colitis with similarities to inflammatory bowel disease in humans developed in severe combined immunodeficiency mice reconstituted with CD45RB(high) CD4+ splenic T cells and could be prevented by cotransfer of CD45RB(low) CD4+ T cells. Inhibition of this Th1 response by the CD45RB(low) T cell population could be reversed in vivo by an anti-transforming growth factor (TGF) beta antibody. Interleukin (IL) 4 was not required for either the differentiation of function of protective cells as CD45RB(low) CD4+ cells from IL-4-deficient mice were fully effective. These results identify a subpopulation of peripheral CD4+ cells and TGF-beta as critical components of the natural immune regulatory mechanism, which prevents the development of pathogenic Th1 responses in the gut, and suggests that this immunoregulatory population is distinct from Th2 cells.